A before and after in the Alto del Cardal archaeological site: A review of recent work on the slopes of the Irazú volcano, Central Valley, Costa Rica - Cavallini, Carolina (2020)
The present work is a review of the recent research carried out at the Alto del Cardal (a.k.a El Cardal) site, based on the pioneering research carried out by the Costa Rican archaeologist Carlos Aguilar Piedra, at the foothills of the Irazú Volcano, especially the work that took place at the archaeological site of Alto del Cardal  during the sixties. The inspection and excavations by Aguilar sought to formulate a chronological sequence for the Central Valley. However, although pioneering, Aguilar's work at El Cardal left large information voids regarding the social groups that inhabited the area, which motivated a revisit and refinement to his work. The research conducted has had the objective of characterizing and establishing the function of this site during Precolumbian times. To accomplish this, a series of visits took place, which included a systematic survey and precise excavations in order to understand the chronology and spatial location of the settlement. The research at El Cardal showed a site that was strategically located in order to mobilize artifacts and people between the Atlantic Watershed and the Central Valley, and that had a chronological depth that differed from what was initially thought. This is an account of old and new work at El Cardal, which implied archival research at the Archaeology Laboratory of the University of Costa Rica and of the information gathered recently by the new investigations at the site.